Fabrication of the magnetic mesoporous silica Fe-MCM-41-A as efficient adsorbent: performance, kinetics and mechanism - Yige Guo (Nature Portfolio, 2021)
Abstract Antibiotics are emerging pollutants and increasingly present in aquaculture and industrial wastewater. Due to their impact on the environment and health, their removal has recently become a significant concern. In this investigation, we synthesized nano zero-valent iron-loaded magnetic mesoporous silica (Fe-MCM-41-A) via precipitation and applied the adsorption of oxytetracycline (OTC) from an aqueous solution. The effects of competing ions such as Na+, Ca2+ and Cu2+ on the adsorption process under different pH conditions were studied in depth to providing a theoretical basis for the application of nanomaterials. The characterization of the obtained material through transmission electron microscopy demonstrates that the adsorbent possesses hexagonal channels, which facilitate mass transfer during adsorption. The loaded zero-valent iron made the magnetic, and was thus separated under an applied magnetic field. The adsorption of OTC onto Fe-MCM-41-A is rapid and obeys the pseudo-second-order kinetic model, and the maximum adsorption capacity of OTC is 625.90 mg g−1. The reaction between OTC and Fe-MCM-41-A was inner complexation and was less affected by the Na+. The effect of Ca2+ on the adsorption was small under acidic and neutral conditions. However, the promotion effect of Ca2+ increased by the increase of pH. Cu2+ decreased the removal efficiencies continuously and the inhibitory effects decrease varied with the increase of pH. We propose that surface complexing, ion-exchange, cationic π-bonding, hydrogen bonding, and hydrophobicity are responsible for the adsorption of OTC onto Fe-MCM-41-A.